The magic of metaphor stories for teachers, trainers & thinkers - Owen, Nick; Lovatt, Mark; Turner, John (United Kingdom : Crown House Publishing Limited, 2009)
This audio presents a collection of stories designed to engage, inspire and transform the listener. Some of the stories motivate, some are spiritual, and some provide strategies for excellence. All promote positive feelings, encouraging confidence, direction and vision
Trainer: Nick Owen
CD-AUDIO Format
Keywords: Educational psychology